Nanofiberous composite with CuO-Ag0 supported on bamboo/lycra for protection against transmittable infectious diseases - Abdul Wahab Jatoi; Faisal Ahmed Memon; Muhammad Ishaque Abro (Next Nanotechnology)
The transmittable infectious diseases, detrimental environmental contaminants and harmful UV radiations remained constant threat to human civilization. Cold, pneumonia, tuberculosis bacteria, rubella virus, RSV and COVID19, then urban and industrial emissions, volcanic eruptions, pollen, aerosols on one hand and skin cancer, sunburn, premature ageing and skin tanning on the other hand are some of the examples of serious risks to health, safety and well-being. The WHO reported over 7million worldwide deaths due to hazardous air contaminants. Exploiting the tremendous features of nanofiberous structure and excellent microbiocidal properties of Ag0 and CuO nanoparticles, a sustainable and stable nanofiber based composite Bmb-nanoNP was developed. Utilization of biocompatible, biodegradable, nontoxic and environmental friendly polymers enabled the composite as sustainable source for protective clothing purposes. The microparticulate filtration of Bmb-nanoNP was 99.13 % and 96 % with and without air suction respectively. The microbiocidal affect against E. coli and S. aureus strains was excellent(5.9 % and 8.86 % cell viabilities respectively). Similarly, the Bmb-nanoNP showed calculated UV protection factor (UPF) of 7954 (50 + rating).These characteristics demonstrated potential candidacy of the Bmb-nanoNP composite for multi-functional safety clothing applications.